Empowering nutrition: Gender-sensitive best practices revealed - Nchanji, Eileen Bogweh; Karanja, David; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Waswa, Boaz Shaban (2024)
The gender-responsive nutrition training conducted by CGIAR Gender Equality Initiative (HER+) has yielded promising results. It has begun to dismantle social norms that hinder food access and consumption, paving the way for a more inclusive and healthier future. The training has successfully engaged men and private and public sector partners, emphasizing the importance of diverse food for all household members. This has been linked to farmers’ access to inclusive crop technologies in the mother-baby demonstrations, own fields, and community food resources.